Dynamics of sleep oscillations is coupled to brain temperature on multiple scales. (13th June 2019) - Csernai, Márton; Borbély, Sándor; Kocsis, Kinga; Burka, Dávid; Fekete, Zoltán; Balogh, Veronika; Káli, Szabolcs; Emri, Zsuzsa; Barthó, Péter
Abstract : Key points: Sleep spindle frequency positively, duration negatively correlates with brain temperature. Local heating of the thalamus produces similar effects in the heated area. Thalamic network model corroborates temperature dependence of sleep spindle frequency. Brain temperature shows spontaneous microfluctuations during both anesthesia and natural sleep. Larger fluctuations are associated with epochs of REM sleep. Smaller fluctuations correspond to the alteration of spindling and delta epochs of infra-slow oscillation. Abstract: Every form of neural activity depends on temperature, yet its relationship to brain rhythms is poorly understood. In this work we examined how sleep spindles are influenced by changing brain temperatures and how brain temperature is influenced by sleep oscillations. We employed a novel thermoelectrode designed for measuring temperature while recording neural activity. We found that spindle frequency is positively correlated and duration negatively correlated with brain temperature. Local heating of the thalamus replicated the temperature dependence of spindle parameters in the heated area only, suggesting biophysical rather than global modulatory mechanisms, a finding also supported by a thalamic network model. Finally, we show that switches between oscillatory states also influence brain temperature on a shorter and smaller scale. Epochs of paradoxical sleep as well as the infra‐slow oscillation were associated with brain temperature fluctuations below 0.2°C. Our results highlight that brain temperature is massively intertwined with sleep oscillations on various time scales. Key points: Sleep spindle frequency positively, duration negatively correlates with brain temperature. Local heating of the thalamus produces similar effects in the heated area. Thalamic network model corroborates temperature dependence of sleep spindle frequency. Brain temperature shows spontaneous microfluctuations during both anesthesia and natural sleep. Larger fluctuations are associated with epochs of REM sleep. Smaller fluctuations correspond to the alteration of spindling and delta epochs of infra-slow oscillation.